Vaksinasi Newcastle Disease pada Peternakan Ayam Buras di Kabupaten Agam Sumatera Barat - Muhammad Zuhdi Badruzzaman; Mochamad Alfinanda Santriagung; Agus Setiyono (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Tetelo or Newcastle disease (ND) is a strategic infectious viral disease that is endemic in Indonesia. Prevention of these diseases by vaccinating poultry as a source of infectious disease. One of the vaccines used for tetelo repeat vaccination is the active tetelo (ND) active vaccine. Active ND vaccine is a vaccine in the frozen dried form which each dose contains 108 EID50 viruses. Repeated vaccination is carried out to trigger secondary antibody responses in native chickens in order to achieve a protective antibody titer against tetelo. One of them is people's fights in Agam Regency, West Sumatera with a population of 184 village chicken. The purpose of the activity is to prevent ND disease (Newcastle disease) on community farms. Vaccination is done by making sometimes where chickens are vaccinated and making nets around the cage. Vaccination results have reached the target of 90% of the chicken population in these farmers. The impact of vaccination will be seen 2-3 days after the vaccination is carried out. The population immunity from chickens from breeders will increase. A factor in the occurrence of ND (Newcastle Desease) due to the close distance between the chicken coop and other poultry cages. Keywords: newcastle desease, vaccination, village chicken